THEORY PLANNED BEHAVIOR APPROACH ON PURCHASE INTENTION OF ENERGY-EFFICIENT HOME APPLIANCES, ECO-LITERACY AS MODERATOR - Elistia Elistia; Fransiska Deodora; Siti Mariam (Yayasan Education and Social Center, 2023)
The activities of human beings have had the effect of worsening the climate of the earth by depleting natural resources and polluting the air, water, and soil. Increasing household electrical appliance growth has increased energy consumption and exacerbated environmental pollution. The behavior of using environmentally friendly household electronic equipment products has become an exciting research topic because it has implications for awareness of the need to target environmentally friendly consumers in purchasing behavior. This study investigates the effect of perceived usefulness, attitude, subjective norms, and perceived behavior control on purchase intention and the moderating effect of eco-literacy concerning energy-saving equipment products. The research method is descriptive causality with a quantitative approach with sample respondents in Jakarta; data were processed and analyzed using Structural Equation Model. The findings of this study indicate that Subjective Norms and Perceived Behavior Control positively affect Purchase Intention. However, Attitude and Perceived Usefulness do not affect purchase intention. Moreover, Eco-literacy positively moderates Subjective Norms. The research contributes to measuring consumer behavior towards environmentally friendly and electronic energy-efficient home appliances so that they have sustainable implications for the environment. Because of this, one of the essential things businesses can do to maintain sustainable relationships, such as reducing their energy consumption and raising public awareness, is to increase their eco-literacy campaigns